ANALISIS KERAGAAN PETANI KELAPA SAWIT POLA PLASMA DI DESA MEKAR JAYA KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR DAN POLA SWADYA DI DESA BUKIT LEMBAH SUBUR KECAMATAN UKUI KABUPATEN PELALAWAN - Pangestu, Priyo; Hutabarat, Sakti; Dewi, Novia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Rapid growth of palm oil demand has provoked land expansion to grow oil palm. However, deforestation caused by land expansion has negative impacts to the environment. Some internaltional non-governmental organizations have established certification program to mitigate these impacts. The objective of Roundtable on Sustainable Palm Oil is to promote sustainable production in Palm Oil supply chain. The standard of RSPO certification consists of Principles and Criteria that must be complied by oil palm growers to be included in Palm Oil supply chain. The objective of this study is to analyse the performance of scheme and independent smallholders, to compare the performance of the two model of smallholders, and to assess the gap between the existing performance and the RSPO standard. Using a survey method the data were collected from selected farmers from the two farmers’ group. The result shows that the performance of scheme smallholders is better than the independent smallholders. The assessment on productivity and farm income also shows that scheme smallholders are higher than the independent smallholders. Finally, the scheme smallholders applied good agricultural practices more than the independent smallholders.   Keywords: Smallholders, performance, income, scheme smallholders, independent smallholers.